Transverse ultrafast laser inscription in bulk silicon - Chambonneau, Maxime; Blothe, Markus; Li, Qingfeng; Fedorov, V. Yu; Heuermann, T.; Gebhardt, Martin; Gaida, Christian; Tertelmann, S.; Sotier, Florian; Limpert, Jens; Tzortzakis, S.; Nolte, Stefan (Physical Review Research, 2021)
In-volume ultrafast laser direct writing of silicon is generally limited by strong nonlinear propagation effects preventing the production of modifications. By using advantageous spectral, temporal, and spatial conditions, we demonstrate that modifications can be repeatably produced inside silicon. Our approach relies on irradiation at wavelength with temporally distorted femtosecond pulses. These pulses are focused in a way that spherical aberrations of different origins mutually balance, as predicted by point spread function analyses and in good agreement with nonlinear propagation simulations. We also establish the laws governing modification growth on a pulse-to-pulse basis, which allows us to demonstrate transverse inscription inside silicon with various line morphologies depending on the irradiation conditions. We finally show that the production of single-pulse repeatable modifications is a necessary condition for reliable transverse inscription inside silicon.
CRIS-Team Scopus Importer:2023-04-20